PENGARUH MODEL LEARNING CYCLE TERHADAP HASIL BELAJAR PADA MATERI PENCEMARAN LINGKUNGAN SISWA KELAS VII DI SMP NEGERI 15 AMBON - Astrid Rhita Jacob; Alwi Smith (BIOPENDIX, 2019)
Background: Education that is used as a forum to develop human potential requires a clear and mature set of systems to be able to deliver people to their potential development. For this reason, development in the education sector must continue to be developed in the direction of improving the quality of education. Method: This study was conducted at SMP Negeri 15 Ambon with a total of 25 students in class VII8. The KKM of SMP 15 Ambon biology subjects is 70. This study uses descriptive analysis to determine the learning outcomes of cognitive, affective, and psychomotor students. Results: Research shows that mastery of biological concepts before the application of the learning cycle model is classified as very low. This can be seen from the average score of achievement in the initial test, which is 40 from KKM. After the application of the learning cycle learning method, the formative test results obtained by students became better with the average percentage of achievement in the formative test increasing by 89. Conclusion: Learning cycle learning method is able to improve student learning outcomes on the concept of environmental pollution